The impact of microalgae chlorella vulgaris and scenedesmus quadricauda on the growth parameters of the ciliate paramecium caudatum - ROSCOV, Elena; TODERAS, Ion; UNGUREANU, Laurentia; TUMANOVA, Daria (One Health & Risk Management, 2024)
Introduction. An important aspect of research in the field of microbial ecology is understanding the interactions between organisms, particularly the influence they have on one another within aquatic ecosystems. Green microalgae (phylum Chlorophyta) represent a diverse group of photosynthetic organisms, playing a significant role in ecological cycles. Investigations have focused on evaluating the impact of two microalgae species, Chlorella vulgaris and Scenedesmus quadricauda, on the growth parameters of the natural population of Paramecium caudatum, making it a suitable indicator for assessing the influence of these organisms on the food chain.Material and methods. The research was based on the work of Kokova, V. (1982), and Likhachev, S.V. (2020). The productivity of the ciliates was determined by their division rate, according to Zaika V.E. (1983) and Spinei L. (2009). Experiments were conducted over intervals of 24-144 hours, using microalgae solution concentrations at 0.1, 0.5, 1, and 10 mg/L.Results. For Chlorella vulgaris the lower doses generated a significant stimulatory effect on P. caudatum, resulting in notable increases in both number and reproduction rate. In contrast, for Scenedesmus quadricauda, lower doses also had a pronounced stimulatory effect, while higher doses yielded varied results, including both increases and decreases in parameters.Conclusions. Both strains of microalgae demonstrate stimulatory potential on the natural population of P. caudatum, particularly at lower doses.